PENGARUH ASIMETRI INFORMASI DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN FOOD AND BEVERAGES YANG GO PUBLIC DI BEI - Rina Moestika Setyaningrum; Aprillia Yunita Sari (STIE Perbanas Surabaya, 2011)
The increasing business development has created the higher economic growth so that it can also affect the degree of competition in the business world. For that reason, there have been some efforts conducted by the business policy makers such as business people and investors to develop their business optimally. They also intend to make their business more effective and efficient not to mention by the manufacturing companies that have been going public. This paper attempts to prove empirically the effect of information asymmetry and the size of companies towards profit management. The financial statements by the food and beverages in manufacturing companies listed at Indonesia Stock Exchange (ISE) are used as the population. They are in the period between 2005 and 2008 with eleven companies. Purposive sampling is used for gathering the data and linear regression is also used for data analysis. It is concluded that the information asymmetry contributes to the profit management approximated by discretionary accruals. In addition, the size of the companies contributes to the lowering profit management approximated by discretionary accruals as well